Flexible and deployable colon support structure for endoluminal interventions - Miyasaka, Muneaki (2021)
When performing endoluminal surgery inside the colon using a flexible endoscopic robot, there is a problem of losing visualization and task space due to the collapsing of the surrounding wall. This happens mainly because of the intra-abdominal pressure and peristalsis of the colon. Although insufflation is commonly used for expanding the colon, it does not function when a full-thickness incision is created on the colon wall. To support the collapsing colon and ensure sufficient visualization and task space even with a hole, we developed a deployable colon support structure (CSS) that can be seamlessly adapted to the existing procedures. While the CSS is designed to be small and flexible enough to pass through an endoscopic channel that can be tortuous, it becomes steady enough to hold the collapsing/squeezing colon after being deployed. Also, the CSS is collapsible after task completion, for retraction through an endoscopic channel. Through the ex-vivo and in-vivo studies with a swine, we have successfully demonstrated the feasibility of supporting the colon wall during endoluminal interventions with the CSS. We confirmed that the CSS was easily deliverable and deployable and the created space was large enough to perform surgical tasks using robotic arms.